At the mountain of God story and theology in Exodus 32-64 - Moberly, R. Walter L. (Sheffield, UK JSOT, 1983)
Includes bibliographical references and index
Keywords: Bible. O.T. Exodus XXXII-XXXIV -- criticism, interpretation, etc